Platelet and haemoglobin levels in patients on isosorbide mononitrate and/or cilostazol with lacunar ischaemic stroke: data from the LACI-1 trial - Appleton, Jason P.; Flaherty, Katie; Blair, Gordon W.; Law, Zhe Kang; Doubal, Fergus; Sprigg, Nikola; Bath, Philip M.; Wardlaw, Joanna M. (2018)
Background: Cilostazol and isosorbide mononitrate (ISMN) have properties that may be of benefit in the context of cerebral small vessel disease and lacunar ischaemic stroke. As both drugs may influence platelet and haemoglobin levels, we sought to assess their effects using data from the lacunar intervention trial-1 (LACI-1).